2019
DOI: 10.3390/ijms20133199
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Saliva: Challenges and Future Perspectives for the Treatment of Xerostomia

Abstract: The chronic sensation of a dry mouth is a disease condition called xerostomia and affects a large part of the population. Xerostomia is associated with decreased secretion, or more often, qualitative changes in saliva proteins and immunoglobulin concentrations that develop as a result of salivary gland dysfunction. Several reasons causing dry mouth were described, and usually, they include taking medications, diseases or radiotherapy. In some situations, when it is difficult to use salivary stimulants or saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 129 publications
1
52
0
5
Order By: Relevance
“…Thus, in this work, the ability of preparation B containing gold-or aminosilane coated magnetic nanoparticles was assessed in vitro, for inhibition of the adhesion and biofilm formation of tested microorganisms co-culturable with oral bacteria (Figure 4). As published previously [14], the evaluation of the ability of artificial saliva preparations to restrict the adhesion process indicated that, in most cases, only substitute B possesses the ability to significantly decrease the attachment of tested microorganisms to the surface. The addition of nanoparticles does not decrease or slightly decrease the adhesion efficacy.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Thus, in this work, the ability of preparation B containing gold-or aminosilane coated magnetic nanoparticles was assessed in vitro, for inhibition of the adhesion and biofilm formation of tested microorganisms co-culturable with oral bacteria (Figure 4). As published previously [14], the evaluation of the ability of artificial saliva preparations to restrict the adhesion process indicated that, in most cases, only substitute B possesses the ability to significantly decrease the attachment of tested microorganisms to the surface. The addition of nanoparticles does not decrease or slightly decrease the adhesion efficacy.…”
Section: Resultssupporting
confidence: 52%
“…Saliva controls the pH around neutrality, in effect creating an environment that is adequate for the growth of many oral microorganisms, and provides a relationship developing between the host and the resident microbiota. However, any perturbation in the flow of saliva, including xerostomia, might cause dysbiosis to occur rapidly [14]. Oral cavity bacteria, specifically those involved in biofilm formation and dental disorders, are major health concerns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parotid gland (PG) is the largest of the three major salivary glands, and its function and structure may be affected by different factors resulting in toxicity and dysfunction (Esfahani et al, 2015). PG dysfunction results in xerostomia that affects other oral tissues causing mucous membrane infections, altered taste, burning tongue, and difficulty in talking and chewing (Lysik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%